1999
DOI: 10.1002/(sici)1099-0992(199908/09)29:5/6<781::aid-ejsp960>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Rage and reason: the psychology of the intuitive prosecutor

Abstract: This study explores the conditions under which experimentally primed anger influences both attributions of responsibility and the processes by which people make such attributions. Drawing on social functional theory, it was hypothesized that people are best thought of as ‘intuitive prosecutors’ who lower their thresholds for making attributions of harmful intent and recommending harsh punishment when they both witness a serious transgression of societal norms and believe that the transgressor escaped punishmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
151
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(158 citation statements)
references
References 26 publications
6
151
1
Order By: Relevance
“…Our results in support of the anger hypothesis are consistent with a growing body of evidence that suggests that people respond to challenges to their worldview with moral outrage and a desire to punish the transgressor (e.g., Goldberg, Lerner, & Tetlock, 1998;Greenberg et al, 1997;Skitka, Bauman, & Mullen, 2004;Tetlock, 2002;Tetlock et al, 2000) and with other research that indicates that discrete emotions function either as a source of moral judgment (Haidt, Koller, & Dias, 1993;Wheatley & Haidt, 2005) or as predictors of moral judgment (Rozin, Lowery, Imada, & Haidt, 1999). For example, Haidt's (2001) social intuitionist model argues that people often make moral judgments quickly and intuitively on the basis of their gut-level reactions and that moral reasoning only comes into play when people are asked to justify their conclusions.…”
Section: Discussionsupporting
confidence: 89%
“…Our results in support of the anger hypothesis are consistent with a growing body of evidence that suggests that people respond to challenges to their worldview with moral outrage and a desire to punish the transgressor (e.g., Goldberg, Lerner, & Tetlock, 1998;Greenberg et al, 1997;Skitka, Bauman, & Mullen, 2004;Tetlock, 2002;Tetlock et al, 2000) and with other research that indicates that discrete emotions function either as a source of moral judgment (Haidt, Koller, & Dias, 1993;Wheatley & Haidt, 2005) or as predictors of moral judgment (Rozin, Lowery, Imada, & Haidt, 1999). For example, Haidt's (2001) social intuitionist model argues that people often make moral judgments quickly and intuitively on the basis of their gut-level reactions and that moral reasoning only comes into play when people are asked to justify their conclusions.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, the role of emotion more generally in people's justice-related thoughts and behavior has been relatively overlooked in recent years (for another early emotion-based perspective, other than just-world theory, see equity theory; e.g., Adams, 1965). An exception to this trend is recent work by Darley and his colleagues (for a review, see Darley, 2002) on the punishment of perpetrators (for some other exceptions, see Feather & Sherman, 2002;Goldberg, Lerner, & Tetlock, 1999;Mikula, Scherer, & Athenstaedt, 1998). Darley, Carlsmith, and their colleagues (e.g., Carlsmith, Darley, & Robinson, 2002;Darley, Carlsmith, & Robinson, 2000) found evidence that the primary goal among laypeople in punishing offenders is a desire to ensure the transgressor gets his or her just desserts; sometimes called a desire for retribution.…”
Section: Just-world Theory and Other Approaches To Social Justicementioning
confidence: 99%
“…Moral anger is associated with concerns about harm and others' rights (Haidt, 2003), as well as with whether justice has been served (Goldberg, Lerner, & Tetlock, 1999) and whether one has acted responsibly (Averill, 1983). While the elicitors of core disgust in non-moral situation appear to largely serve as cues to contagious disease; somewhat different elicitors of disgust apply in moral contexts (Marzillier & Davey, 2004;Simpson, Carter, Anthony, & Overton, 2006).…”
Section: Anger and Disgustmentioning
confidence: 99%
“…For example, Goldberg, Lerner and Tetlock (1999) found that once participants learned that justice had been served, this decreased anger and no longer influenced future judgments. Research has also found that the anger experience is influenced by one's relationship to the target (e.g., Fischer & Roseman, 2007;Weber, 2004), and that anger is influenced by abstract contextual cues, such as harm and intentionality, while disgust only responds categorically to whether or not a bodily norm violation has occurred (Russell & Giner-Sorolla, 2009; see also Gutierrez & Giner-Sorolla, 2007 There appears to be a functional difference between anger and disgust as well.…”
Section: Anger and Disgustmentioning
confidence: 99%